Trends in US Outpatient Antibiotic Prescriptions During the Coronavirus Disease 2019 Pandemic. (29th December 2020) - King, Laura M; Lovegrove, Maribeth C; Shehab, Nadine; Tsay, Sharon; Budnitz, Daniel S; Geller, Andrew I; Lind, Jennifer N; Roberts, Rebecca M; Hicks, Lauri A; Kabbani, Sarah
Abstract: Background: The objective of our study was to describe trends in US outpatient antibiotic prescriptions from January through May 2020 and compare with trends in previous years (2017–2019). Methods: We used data from the IQVIA Total Patient Tracker to estimate the monthly number of patients dispensed antibiotic prescriptions from retail pharmacies from January 2017 through May 2020. We averaged estimates from 2017 through 2019 and defined expected seasonal change as the average percent change from January to May 2017–2019. We calculated percentage point and volume changes in the number of patients dispensed antibiotics from January to May 2020 exceeding expected seasonal changes. We also calculated average percent change in number of patients dispensed antibiotics per month in 2017–2019 versus 2020. Data were analyzed overall and by agent, class, patient age, state, and prescriber specialty. Results: From January to May 2020, the number of patients dispensed antibiotic prescriptions decreased from 20.3 to 9.9 million, exceeding seasonally expected decreases by 33 percentage points and 6.6 million patients. The largest changes in 2017–2019 versus 2020 were observed in April (–39%) and May (–42%). The number of patients dispensed azithromycin increased from February to March 2020 then decreased. Overall, beyond-expected decreases were greatest among children (≤19 years) and agents used for respiratory infections, dentistry, and surgical prophylaxis. Conclusions: From January 2020 to May 2020, the number of outpatients with antibiotic prescriptions decreased substantially more than would be expected because of seasonal trends alone, possibly related to the coronavirus disease 2019 pandemic and associated mitigation measures. Abstract : From January to May 2020, the number of outpatients dispensed antibiotic prescriptions decreased substantially more than seasonally expected, likely related to the coronavirus disease 2019 pandemic. Decreases were greatest among children and agents frequently prescribed for respiratory infections, dentistry, and surgical prophylaxis.